Kajian Suprasegmental dalam Bahasa Arab: Analisis Penggunaan Nada dan Intonasi dalam Khutbah Habib Umar - Umam, Maulid Hotibul (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of intonation and tone in shaping the effectiveness of religious speeches, particularly focusing on the khutbahs delivered by Habib Umar bin Hafidz. Using a qualitative approach, the study examines a selected video of a khutbah to assess the influence of various tonal and intonational patterns on the speech’s impact. The research finds that intonation plays a crucial role in conveying emotion, urgency, and clarity, enhancing the listener’s understanding and engagement. The findings highlight the importance of tone variation in delivering messages that resonate deeply with the audience, particularly in religious contexts. This article contributes to the understanding of prosody in religious discourse and offers insights into how intonation can be strategically used to strengthen communication. By addressing the gap in previous studies on the phonological aspects of religious speeches, this research paves the way for future investigations into the relationship between language and its affective impact on listeners.